Ekumenika as wetenskaplike dissipline en die verhouding daarvan tot Ekumeniese Teologie - Crafford, D. (Verbum et ecclesia, 1991)
Ecumenical Studies as a scientific discipline and its relation to ecumenical theology An effort is made to define ecumenism as a comprehensive process. A description is given of the specific character and contents of Ecumenical Studies as theological discipline as well as ecumenical theology as a particular approach to theology. Proposals of how each theological discipline can be practised from an ecumenical viewpoint are given. The article closes with a discussion of the relationship between Ecumenical Studies and ecumenical theology.